2022
DOI: 10.3390/pharmaceutics14020254
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation, Release, and Cytotoxicity of Doxorubicin Loaded in Liposomes, Micelles, and Metal-Organic Frameworks: A Review

Abstract: Doxorubicin (DOX) is one of the most widely used anthracycline anticancer drugs due to its high efficacy and evident antitumoral activity on several cancer types. However, its effective utilization is hindered by the adverse side effects associated with its administration, the detriment to the patients’ quality of life, and general toxicity to healthy fast-dividing cells. Thus, delivering DOX to the tumor site encapsulated inside nanocarrier-based systems is an area of research that has garnered colossal inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 136 publications
1
29
0
Order By: Relevance
“…These values are comparable with the values for similar nanocarriers reported in the literature. 42 In the fluorescence spectrum of DOX@ p (MVCA-AlT), a decrease in the intensity of the DOX emission is observed, compared with free DOX, because of quenching effects 43 (Fig. 2(b)).…”
Section: Resultsmentioning
confidence: 97%
“…These values are comparable with the values for similar nanocarriers reported in the literature. 42 In the fluorescence spectrum of DOX@ p (MVCA-AlT), a decrease in the intensity of the DOX emission is observed, compared with free DOX, because of quenching effects 43 (Fig. 2(b)).…”
Section: Resultsmentioning
confidence: 97%
“…Doxorubicin is commonly used as an anticancer agent. However, it is resisted by cancer cells and has toxic effects on healthy fast-dividing cells [ 22 ]. Melittin, a peptide component of honeybee venom, has a short bloodstream half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies using recombinant TRAIL anchored to the surface of liposomes (LUV-TRAIL) demonstrated that this new formulation was much more potent than soluble TRAIL both in different tumor types both in vitro and in vivo [ 22 , 23 , 24 ]. Although the liposomes for disease treatment have been extensively used in different diseases, liposomes have also been used as a vehicle to encapsulate drugs [ 28 , 29 , 30 ], or more recently, mRNA in vaccine development [ 31 ]. However, attachment of bioactive compounds on the liposome surface has been a less explored therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%